Cerebellar Pathology in Childhood-Onset vs. Adult-Onset Essential Tremor - Louis, Elan D. (Neurosci Lett, 2017)
Although the incidence of ET increases with advancing age, the disease may begin at any age, including childhood. The question arises as to whether childhood-onset ET cases manifest the same sets of pathological changes in the cerebellum as those whose onset is during adult life. We quantified a broad range of postmortem features (Purkinje cell [PC] counts, PC axonal torpedoes, a host of associated axonal changes [PC axonal recurrent collateral count, PC thickened axonal profile count, PC axonal branching count], heterotopic PCs, and basket cell rating) in 60 ET cases (11 childhood-onset and 49 adult-onset) and 30 controls. Compared to controls, childhood-onset ET cases had lower PC counts, higher torpedo counts, higher heterotopic PC counts, higher basket cell plexus rating, and marginally higher PC axonal recurrent collateral counts. The median PC thickened axonal profile count and median PC axonal branching count were two to five times higher in childhood-onset ET than controls, but the differences did not reach statistical significance. Childhood-onset and adult-onset ET had similar PC counts, torpedo counts, heterotopic PC counts, basket cell plexus rating, PC axonal recurrent collateral counts, PC thickened axonal profile count and PC axonal branching count. In conclusion, we found that childhood-onset and adult-onset ET shared similar pathological changes in the cerebellum. The data suggest that pathological changes we have observed in the cerebellum in ET are a part of the pathophysiological cascade of events in both forms of the disease and that both groups seem to reach the same pathological endpoints at a similar age of death.